2002
DOI: 10.1145/504087.504089
|View full text |Cite
|
Sign up to set email alerts
|

On fault classes and error detection capability of specification-based testing

Abstract: In a previous paper, Kuhn [1999] showed that faults in Boolean specifications constitute a hierarchy with respect to detectability, and drew the conclusion that missing condition faults should be hypothesized to generate tests. However this conclusion was premature, since the relationships between missing condition faults and faults in other classes have not been sufficiently analyzed. In this note, we investigate such relationships, aiming to complement the work of Kuhn. As a result, we obtain an extended hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 2 publications
4
57
0
Order By: Relevance
“…It is shown that ENF are the weakest faults in the sense that any test technique that catches stronger faults is very likely to find ENFs. The results have been further improved by Tsuchiya and Kikuno [27].…”
Section: Related Workmentioning
confidence: 89%
See 1 more Smart Citation
“…It is shown that ENF are the weakest faults in the sense that any test technique that catches stronger faults is very likely to find ENFs. The results have been further improved by Tsuchiya and Kikuno [27].…”
Section: Related Workmentioning
confidence: 89%
“…In the past, various types of faults have been defined and used to study effectiveness of test criteria; see for example [16,22,25,30,33]. An analysis of various fault classes and the hierarchy among them is presented in [15,27].…”
Section: Types Of Faultsmentioning
confidence: 99%
“…Tsuchiya and Kikuno extended Kuhns three fault classes to include the fault class of a missing condition [24]. Lau and Yu further extended Kuhns hierarchy by analyzing the relationships between variable faults and literal faults [25].…”
Section: Fault Classes and Fault Coverages Of Testsmentioning
confidence: 99%
“…VRF is further classified as MCF (Missing Condition Fault) and ICF (Incorrect Condition Fault). Tsuchiya and Kikuno [39] further extended Kuhn's hierarchy by analysing the relationship between VRF and MCF, namely (1) M CF ⇒ V N F , when the fault happens to the same variable; (2) V RF ⇒ M CF when the fault happens to the same variable and the faulty term has more than one variable. The identified hierarchy only considers variable related faults, which means all occurrences of a missing or referenced variable in the expression.…”
Section: Fault Classes and Their Detection Hierarchymentioning
confidence: 99%